Effects of Dietary Docosahexaenoic Acid (DHA) Levels on Growth Performance, Fatty Acid Profile, and NF-κB/Nrf2 Pathway-Related Gene Expression of Razor Clam Sinonovacula constricta - Yuxiang Zhu; Kai Liao; Hailong Huang; Yang Liu; Yang Zhang; Deshui Chen; Bin Ma; Jilin Xu (Aquaculture Nutrition)
Dietary docosahexaenoic acid (DHA) is crucial for the optimal (Opt) growth of bivalves, but the precise dietary DHA requirement remains undetermined in bivalves. Our study identifies the optimal dietary DHA requirement for razor clam Sinonovacula constricta and demonstrates its effects on fatty acid profiles and gene expression related to inflammation and detoxification. Microencapsulated feeds with different DHA levels (DHA1–6 groups: 1.68, 4.85, 9.49, 12.6, 15.59, and 16.95 mg g−1 dry matter) were prepared using spray drying. Razor clams (initial wet weight: 3.8 ± 0.6 mg) were fed these microcapsules for a period of 20 days. The present study showed that the clams in the DHA1 group exhibited significantly lower weight and shell length gain rates compared to those in the DHA3, DHA4, DHA5, and DHA6 groups. Based on the shell length gain rate, the Opt dietary requirement of DHA for clam is approximately 6.42 mg g−1 dry matter. The clams in the DHA2 group had significantly higher crude lipid content compared to those in the DHA1 and DHA6 groups, while the clams in the DHA1 group had the highest ash content, significantly higher than that in the DHA4 and DHA6 groups. The DHA levels in the clams increased with the increase in DHA content in the microcapsules, while the levels of total n-6 polyunsaturated fatty acids (PUFAs), linoleic acid (LA), and alpha-linolenic acid (ALA) decreased. The mRNA levels of cyclooxygenase-2 (cox2) and 5-lipoxygenase type 2 (5-lox-2) were higher in the DHA1 and DHA6 groups compared to other microcapsule groups. As dietary DHA levels increased, the mRNA levels of nuclear factor kappa B (nfκb) and nuclear factor erythroid 2-related factor 2 (nrf2) decreased. Additionally, the mRNA levels of glutamate-cysteine ligase catalytic subunit (gclc) and glutathione S-transferase (gst) were highest in the DHA1 group. This is the first study to determine the Opt DHA requirement for juvenile razor clams using microcapsules with different DHA levels, and this study further reveals that dietary DHA can help reduce inflammation and oxidative status in clams.